Variação espaço-temporal de microplásticos nas águas superficiais de um estuário urbano no nordeste do Brasil - Barbosa, Francisco das Chagas Silva (2024)
Urban estuaries are characterized by receiving a large influx of pollutants, as a result of factors related to land use and occupation in their surroundings, thus serving as a gateway for various contaminants into the oceans, originating from the discharge of effluents, solid waste, and surface runoff. Among these contaminants, microplastics (synthetic polymers ranging in size from 1 μm to 5 mm) have gained considerable attention due to their potential to cause obstruction of the gastrointestinal tract of aquatic animals, bioaccumulation, and biomagnification of micropollutants. The aim of this study is to evaluate the longitudinal and temporal profile of microplastics in the waters of the Cocó River estuary (Fortaleza-CE). Samples were collected at three points distributed along the estuary during dry (October/2021) and rainy (April/2022) seasons. Sampling was performed using a 120 μm plankton net equipped with buoys and a flow meter. Drifts lasted for one minute with the net positioned on the side of the boat. The material retained in the collector cup was immediately transferred to glass jars and stored at -20°C until laboratory analysis. The analytical procedure involved organic matter digestion, density separation, and filtration. Microplastics counting and characterization from the filters were performed by visualization under a stereomicroscope. All steps followed contamination control procedures. During the dry period, an average abundance of 5.68 ± 3.16 items/m3 was observed, which did not differ statistically from the value found during the rainy period, registering an average of 6.45 ± 2.84 items/m3. During the dry period, abundances varied significantly, with the highest value at the collection point located in the upper estuary (8.37 ± 3.56 items/m3), decreasing towards the lower estuary (1.86 ± 0.55 items/m3). During the rainy period, higher abundance was found at the mouth (8.98 ± 3.5 items/m3), and the lowest at the sampling point located in the middle estuary (3.80 ± 0.98 items/m3). In both periods, fibers (53.6%) and fragments (27.4%) were the most common forms encountered. Microplastics smaller than 1 mm were the most prevalent, comprising 65% of the total. A variety of colors were observed, with transparent (30%), blue (20%), black (14,6%), and white (14,9%) being the most common. It is concluded that the Cocó River estuary does not export MPs to the ocean during the dry period, but it cannot be affirmed that the same phenomenon occurs during the rainy period.